2010
DOI: 10.1029/2009ja014641
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and QBO variations in the OH nightglow emission observed by TIMED/SABER

Abstract: [1] Using TIMED/SABER observations, we present global distribution of the semiannual oscillation (SAO), annual oscillation (AO), and quasi-biennial oscillation (QBO) in the OH nightglow peak emission rate and height as well as the intensity. The latitudinal variations of the SAO, AO, and QBO in the peak emission rate are similar to those in the intensity. For the peak emission rate and the intensity, the SAO and QBO amplitudes have three peaks (one at the equator and others at about 35°S and 35°N). The AO ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 43 publications
12
58
0
Order By: Relevance
“…An apparent SAO seems to dominate the OH * emission pattern, especially at the equatorial and midlatitudes, and a strong phase propagation of the oscillation towards the poles can be observed. It can also be seen that the OH * emission does not show a constant SAO phase as a function of latitude (see also Gao et al, 2010), similar to the analyzed VLF data. We examined the OH * data (1 • width) at the latitudes that match the middle of the two transmitterreceiver GCPs, during the same time period as the VLF data (2005-2010 for DN-NWC, and 2009-2012 for MH-NSY), by using Eq.…”
Section: The Vlf Sao Phase and Its Comparison With Satellite Datasupporting
confidence: 58%
See 2 more Smart Citations
“…An apparent SAO seems to dominate the OH * emission pattern, especially at the equatorial and midlatitudes, and a strong phase propagation of the oscillation towards the poles can be observed. It can also be seen that the OH * emission does not show a constant SAO phase as a function of latitude (see also Gao et al, 2010), similar to the analyzed VLF data. We examined the OH * data (1 • width) at the latitudes that match the middle of the two transmitterreceiver GCPs, during the same time period as the VLF data (2005-2010 for DN-NWC, and 2009-2012 for MH-NSY), by using Eq.…”
Section: The Vlf Sao Phase and Its Comparison With Satellite Datasupporting
confidence: 58%
“…The OH * airglow layer peaks around 87 km (Baker and Stair Jr., 1988), in the altitude vicinity of the VLF nighttime reflection height. We used the 2.0 µm data as they are a direct measure of the chemical reaction which creates the OH * (Mlynczak, 1999;Mlynczak et al, 2013) and are tightly linked to atomic oxygen abundance as well as MLT dynamics (Gao et al, 2010;Marsh et al, 2006). A 60-day running-mean of the data was created, in order to obtain good local time coverage (Marsh et al, 2006).…”
Section: The Vlf Sao Phase and Its Comparison With Satellite Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the absolute peak altitudes are known to vary with season (Gao et al, 2010), they can be taken as constant on the timescales of a few minutes over which this experiment was executed. With a steady-state OH model driven using a neutral atmosphere from the Naval Research Laboratory Mass Spectrometer and Incoherent Scatter Radar Empirical model (NRLMSISE) (Picone et al, 2002), the altitude of the (9,7) transition was fixed.…”
Section: Temperature Gradientmentioning
confidence: 99%
“…In addition, sudden stratospheric warmings alter the OH altitude, producing up to 10 km vertical shifts during the descent phase (Shepherd et al, 2010b). On a medium timescale, the seasonal variation in the emission altitudes exhibits semiannual, annual and quasi-biennial oscillations with up to 1.0, 1.5 and 0.5 km amplitudes, respectively (Winick et al, 2009;Gao et al, 2010;Sheese et al, 2014;von Savigny, 2015;Reid et al, 2017). Ghodpage et al (2016) and Sivakandan et al (2016) reported a year-to-year monthly mean OH altitude variation of 2-3 km and attributed it to the effect of the El Niño-Southern Oscillation (ENSO).…”
Section: Introductionmentioning
confidence: 99%